Predicting mathematics performance from anxiety, enjoyment, value, and self-efficacy beliefs towards mathematics among engineering majors - Getahun, Dawit Asrat; Adamu, Getachew; Andargie, Awoke; Mebrat, Jejaw Demamu (Bahir Dar Journal of Education, 2016)
The purpose of this study was to examine first year students’ mathematics anxiety, enjoyment of mathematics, value of mathematics, self-efficacy beliefs and prior performance as predictors of performance on a first year university mathematics course (Applied mathematics I). Data were collected from 225 first year undergraduate students at Bahir Dar University at the beginning and at the end of the course. A rating scale measuring anxiety (11 items), enjoyment of mathematics (14 items), value of mathematics (14 items), mathematics problem solving self-efficacy (9 items) and mathematics tasks self-efficacy (9 items) was used to collect data. The items were adapted from the literature. The participants’ prior performance was assessed by preparing a test from contents of high school mathematics and their performance on the Applied Mathematics course was measured by preparing a test consisting of representative items from the chapters of the course. One-sample t-tests and multiple regression analyses were used to analyze the data. Results revealed that the participants had lower mathematics anxiety, higher level of mathematics enjoyment and value of mathematics. But self-efficacy beliefs were found to be below expected levels. Results from the regression analyses depicted that mathematics enjoyment and mathematics tasks self-efficacy were found to be significant predictors of mathematics problem solving selfefficacy. On the other hand, prior achievement (performance on pre-university mathematics) and self-efficacy beliefs were found to be significant predictors of performance on the university mathematics course. The results imply the need for enhancing students’ self-efficacy beliefs so as to promote their mathematics performance.